The Horizon of Expectation for an Implicit Reader A Critical Review on the Book Nazaruyat Alqira'at Walta'awyl Al'adabii Waqadaya (Reading Theories and Literary Interpretation and Its Issues) - Omid Izanloo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Reader-response criticism is a new method of critique which tries to investigate the reader and the literary texts through a new attitude. The birth of this theory was the result of the intersection of the author-centered approach and the text-centered approach. The contemporaneity of the subject indicates the necessity of examining the subject and Hassan Mustafa Sahloul tries to answer this necessity in Nazaruyat Alqira'at Walta'awyl Al'adabii Waqadaya book. The criticism of nazaruyat Alqira'at Walta'awyl Al'adabii Waqadaya with a descriptive-analytical method shows that Hassan Mustafa Sahloul scrutinized the reader-response criticism approach. This book is written in an introduction and six chapters with in a small number of pages. The contents of the book are simplified in a way that is easily understood by the audience but a large number of chapters and titles has caused the dispersion and incoherence of the most important issues in this theory and in practice, the reader of the book cannot have a coherent classification of this theory and its related branches. There is no precise reference in the text of the book and this makes the reader of the book not know which sources to refer to for the rest of the study in this field. Also, the author has not examined the origin of this theory and its thinkers, and the ideas of some thinkers in the field of reading criticism have also been neglected.